Molecular Dynamics Simulation of the Interaction Between Benzanthrone Dye and Model Lipid Membranes - Zhytniakivska, Olga (East European Journal of Physics, 2020)
The benzanthrone fluorescent dyes are known as environmentally-sensitive reporters for exploring the physicochemical properties and structural alterations of lipid membranes. In the present work the 100-ns molecular dynamics simulation (MD) was used to characterize the bilayer location and the nature of interactions between the benzanthrone fluorescent dye ABM and the model lipid membranes composed of the zwitterionic lipid phosphatidylcholine (PC) and its mixtures with the anionic lipid phosphatidylglycerol (PG20) and sterol cholesterol (Chol30). The MD simulations were performed in the CHARMM36m force field using the GROMACS package. The ABM molecule, which was initially placed at a distance of 30 Å from the midplane of the lipid bilayer, after 10 ns of simulation was found to be completely incorporated into the membrane interior and remained within the lipid bilayer for the rest of the simulation time. The analysis of the MD simulation results showed that the lipid bilayer location of the benzanthrone dye ABM depends on the membrane composition, with the distance from bilayer center being gradually shifted from 0.78 nm in the neat PC bilayer to 0.95 nm and 1.5 nm in the PG- and Chol-containing membranes, respectively. In addition, the partitioning of the ABM into the neat PC bilayer was followed by the probe translocation from the outer membrane leaflet to the inner one. A separate series of MD simulations was aimed at examining the ABM influence on the lipid bilayer structure. It was found that ABM partitioning into the lipid bilayers of various composition has no significant effect on the orientation of the fatty acid chains and leads only to a small increase of the deuterium order parameter for the carbon atoms 5-to-8 in the sn-2 acyl chains of the neat PC membranes. In addition, the interaction of the ABM with the model lipid membranes caused the slight decrease of the surface area per lipid pointing to the slight increase of the packing density of lipid molecules in the presence of ABM. The results obtained provide a basis for deeper understanding of the membrane interactions of benzanthrone dyes and may be useful for the design of the novel fluorescent probes for membrane studies.